Hometown advantage: The effects of monitoring institution location on financial reporting discretion - Ayers, Benjamin C.; Ramalingegowda, Santhosh; Eric Yeung, P. (Journal of Accounting and Economics, 2011)
We examine the impact of institutional ownership on financial reporting discretion, focusing on whether the impact varies with institutions' cost of acquiring monitoring information. Using geographic distance between the firm and the institutional investor as a proxy for the cost of acquiring monitoring information, we find that corporate managers are less likely to use financial reporting discretion in the presence of local monitoring institutions than distant monitoring institutions. We also find that the impact of monitoring institutions on financial reporting discretion varies with the costs and benefits of financial reporting discretion.